Health-related Quality of Life in Patients with Achondroplasia after Global Limb-lengthening Surgery: A Case Series - Ignacio Ginebreda; Maximiliano Ibáñez; Nicole Canu; Carolina Echavarria; Joana Lebre; Miriam Pérez (Journal of Limb Lengthening & Reconstruction)
Background: Achondroplasia can impact daily activities and impair quality of life (QoL). Surgical lengthening of the upper and lower limbs has been reported to increase independence and improve QoL, but further evidence is needed to allow well-informed treatment decisions. Question/Purpose: (1) What height and limb-length improvements are achieved with global limb-lengthening surgery? (2) Does global limb-lengthening surgery improve patient QoL? (3) What major complications are observed with global limb lengthening? Subjects and Methods: This retrospective case series reviewed patients with achondroplasia who underwent global (tibial, femoral, and humeral) elongation between 1986 and 2012 at our institution. Patients were followed for 3 years postoperatively to measure gains in height and limb length. Postelongation QoL was assessed with the 36-item short form health survey (SF-36) and compared with a historical nonsurgical control group. Results: After global lengthening in 35 patients (210 segments), mean increases in limb length (right and left, respectively) were 15.0 and 15.3 cm for the tibia, 14.1 and 14.1 cm for the femur, and 10.8 and 10.9 cm for the humerus, gaining in average 29 cm from lengthening the lower extremities. When compared with a control group (short stature who did not receive limb-lengthening surgery [n = 44]), our patients reported significantly higher mean scores across all eight SF-36 subscales (P < 0.0001 for all subscales). Major complications were reported for 62.2% of patients, most commonly valgus axial deviation of the tibia (both tibias in 24.3%), early consolidation of the tibia (8.1%), and postelongation fracture of the femur (8.1%). Conclusion: Global limb lengthening achieved significant improvements in patient-reported functional and emotional QoL compared with historical nonsurgical controls and an acceptable rate of major complications.